DETERMINASI PROFITABILITAS LPD DI KECAMATAN BEBANDEM - I Nyoman Kasih; Ni Luh Putu Wiagustini (Journal of Applied Management Studies, 2021)
This research was conducted aiming to analyze the effect of Capital Adequacy Ratio (CAR), the amount of credit, and third party funds (DPK) on profitability in the LPD of Bebandem District. This research is an associative research, namely the causality relationship between CAR, the amount of credit, and third party funds on profitability. The data used in this study are secondary data in the form of CAR data, the amount of credit, and third party funds that can be obtained in the Karangasem Regency LPLPD. The data collection method used in this study is a non-participant observation method that is observing CAR data documents, the amount of credit, third party funds and profitability in LPD Bebandem District in 2016-2018. The data analysis technique in this study was quantitative statistical analysis using multiple linear regression models that were completed with the SPSS (Statistical Package for the Social Science) for windows The results of hypothesis testing conducted using multiple linear regression models indicate that: 1). CAR has a positive effect on profitability. 2). Credit has a positive effect on profitability. 3). DPK has a positive effect on profitability. The implications of this study are 1). CAR has a significant positive effect on profitability. This shows a fairly good financial performance on the part of the LPD. 2). Credit has a significant positive effect on profitability. Giving maximum credit to the community will be able to increase LPD income in Bebandem District. 3) DPK has a significant effect on profitability. The more funds that can be collected from the community, it will increase the ability of the LPD to extend credit to the public. With the increased ability to extend credit, LPD revenues will also increase. Therefore, the amount of third party funds raised by the LPD will determine the level of profitability